2019
DOI: 10.1111/jnp.12193
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorders in Parkinson's disease versus in healthy controls: A different predictive model

Abstract: Impulse control disorders (ICDs), including compulsive gambling, buying, sexual behaviour and eating, are not only a severe disorder that can affect the general, nonclinical population, but also a serious, increasingly recognized psychiatric complication in Parkinson's disease (PD). Previous research detected some risk factors for their occurrence in PD patients and in the general population, including impulsivity. However, impulsivity is a multidimensional construct that comprises several aspects, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…ICD symptoms in newly diagnosed drug-naïve PD patients actually seem to be comparable to that of the general population, around 20% (Antonini et al, 2011;Weintraub et al, 2013). However, recent research has suggested a difference in the nature of ICRBs among these populations, whereby delay discounting (with preference for smaller and more immediate rewards over larger but more delayed rewards) and deficits in reflection impulsivity (ability to collect sufficient information prior to decision-making) better predict ICDs in the PD and general populations, respectively (Izzo et al, 2020).…”
Section: Mechanisms Underlying Pd + Icd: Human Studiesmentioning
confidence: 98%
“…ICD symptoms in newly diagnosed drug-naïve PD patients actually seem to be comparable to that of the general population, around 20% (Antonini et al, 2011;Weintraub et al, 2013). However, recent research has suggested a difference in the nature of ICRBs among these populations, whereby delay discounting (with preference for smaller and more immediate rewards over larger but more delayed rewards) and deficits in reflection impulsivity (ability to collect sufficient information prior to decision-making) better predict ICDs in the PD and general populations, respectively (Izzo et al, 2020).…”
Section: Mechanisms Underlying Pd + Icd: Human Studiesmentioning
confidence: 98%
“…To model alterations in decision making seen in impulse control disorder (ICD), we took advantage of a normal cognitive phenomenon, delay discounting, in which the value of a reward is discounted by the time needed to wait for it (32). Delay discounting behavior is abnormal in individuals with ICD, with more pronounced discounting, or intolerance for delays (10)(11)(12). We adapted a rodent delay discounting task for use in healthy and parkinsonian mice (Fig.…”
Section: Treatment With the Dopamine Agonist Pramipexole Causes Impul...mentioning
confidence: 99%
“…While visual modality is the most common presentation of hallucinations in all three conditions (49-51), delusional content may differ, with paranoid delusions more commonly found in DLB and grandiose types in BSD (53). Impulsivity is a core feature of BSD that leads to engagement in risky behaviors, especially during the manic/hypomanic phases (3,54) and is also present in parkinsonian patients (55). However, for decades, parkinsonian ICDs have been attributed to iatrogenic side effects of Dopamine Agonist therapies (56)(57)(58)(59)(60)(61)(62)(63)(64), before being recognized as a core symptom of the disease, appearing often before any exposition to drug treatments.…”
Section: Parkinson's Disease and Dementia With Lewy Bodies Clinical O...mentioning
confidence: 99%